2023
DOI: 10.1093/bib/bbad180
|View full text |Cite
|
Sign up to set email alerts
|

P-CSN: single-cell RNA sequencing data analysis by partial cell-specific network

Abstract: Although many single-cell computational methods proposed use gene expression as input, recent studies show that replacing ‘unstable’ gene expression with ‘stable’ gene–gene associations can greatly improve the performance of downstream analysis. To obtain accurate gene–gene associations, conditional cell-specific network method (c-CSN) filters out the indirect associations of cell-specific network method (CSN) based on the conditional independence of statistics. However, when there are strong connections in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Many tools, such as MetaCell (Baran et al, 2019 ), MC2 (Ben-Kiki et al, 2022 ), SuperCell (Bilous et al, 2022 ) and SEACells (Persad et al, 2023 ), are available to build metacells. Metacells have been effectively employed in various studies for multiple types of downstream analyses (Li et al, 2019 ; Giladi et al, 2018 ; Cohen et al, 2018 ; Bornstein et al, 2018 ; Zheng et al, 2021b ; Cohen et al, 2022 ; Liu et al, 2021b ; Nguyen et al, 2020 ; Magaletta et al, 2022 ; Wang et al, 2023 ; Luo et al, 2021 , 2023 ), and have demonstrated utility in the analysis and representation of single-cell atlases (Zheng et al, 2021b ; Han et al, 2023 ; Imaz-Rosshandler et al, 2024 ). Moreover, metacells have been used to scale existing computational methods to larger datasets (Wagner et al, 2021 ; Qian et al, 2022 ; Hristov et al, 2022 ) and to enhance their robustness and interpretability (Liu et al, 2021b ; Nguyen et al, 2020 ; Magaletta et al, 2022 ; Wang et al, 2023 ; Persad et al, 2023 ; Argelaguet et al, 2022 ; Luo et al, 2021 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many tools, such as MetaCell (Baran et al, 2019 ), MC2 (Ben-Kiki et al, 2022 ), SuperCell (Bilous et al, 2022 ) and SEACells (Persad et al, 2023 ), are available to build metacells. Metacells have been effectively employed in various studies for multiple types of downstream analyses (Li et al, 2019 ; Giladi et al, 2018 ; Cohen et al, 2018 ; Bornstein et al, 2018 ; Zheng et al, 2021b ; Cohen et al, 2022 ; Liu et al, 2021b ; Nguyen et al, 2020 ; Magaletta et al, 2022 ; Wang et al, 2023 ; Luo et al, 2021 , 2023 ), and have demonstrated utility in the analysis and representation of single-cell atlases (Zheng et al, 2021b ; Han et al, 2023 ; Imaz-Rosshandler et al, 2024 ). Moreover, metacells have been used to scale existing computational methods to larger datasets (Wagner et al, 2021 ; Qian et al, 2022 ; Hristov et al, 2022 ) and to enhance their robustness and interpretability (Liu et al, 2021b ; Nguyen et al, 2020 ; Magaletta et al, 2022 ; Wang et al, 2023 ; Persad et al, 2023 ; Argelaguet et al, 2022 ; Luo et al, 2021 , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an aggregation of profiles of highly similar cells for GRN analysis was used even before the introduction of the metacell concept (Pliner et al, 2018 ). Currently, the metacell concept is used to enhance signal for GRN construction for scRNA-seq (Liu et al, 2021b ; Nguyen et al, 2020 ; Magaletta et al, 2022 ; Wang et al, 2023 ) and for sparser single-cell lncRNA-seq data (Luo et al, 2021 , 2023 ).…”
Section: Applications Of Metacellsmentioning
confidence: 99%
“…For this reason, an aggregation of profiles of highly similar cells for GRN analysis was used even before the introduction of the metacell concept 99 . Currently, the metacell concept is used to enhance signal for GRN construction for scRNA-seq 100103 , for more sparse single-cell lncRNA-seq data 104,105 and for multi-omics data 106 . Given the computational cost of GRN analysis 17 , metacells facilitate scaling of GRN construction tools, particularly those initially developed for bulk RNA-seq 48 , to handle larger datasets 100 .…”
Section: Applications Of Metacellsmentioning
confidence: 99%